Pharmacological Inhibition of BAD Ser99 Phosphorylation Enhances the Efficacy of Cisplatin in Ovarian Cancer by Inhibition of Cancer Stem Cell-like Behavior - Wang, Yanxin (AMER CHEMICAL SOC, 2023)
10.1021/acsptsci.0c00064